Saving Food : Production, Supply Chain, Food Waste and Food Consumption - Galanakis, Charis M. (Academic Press, an imprint of Elsevier, 2019)
Saving Food: Production, Supply Chain, Food Waste and Food Consumption presents the latest developments on food loss and waste. Emphasis is placed on global issues, the environmental impacts of food consumption and wasted food, wasted nutrients, raising awareness via collaborative networks and actions, the effect of food governance and policy in food losses, promotion of sustainable food consumption, food redistribution, optimizing agricultural practices, the concept of zero waste, food security and sustainable land management, optimizing food supply and cold chains, food safety in supply chain management, non-thermal food processing/preservation technologies, food waste prevention/reduction, food waste valorization and recovery. Intended to be a guide for all segments of the food industry aiming to adapt or further develop zero waste strategies, this book analyzes the problem of food waste from every angle and provides critical information on how to minimize waste.